2014
DOI: 10.1152/japplphysiol.01160.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical stimulation of the feet on gait and cardiovascular autonomic control in Parkinson's disease

Abstract: Motor impairment in Parkinson's disease (PD) is partly due to defective central processing of lower limb afferents. Concomitant alterations in cardiovascular autonomic control leading to orthostatic hypotension may worsen motor ability. We evaluated whether mechanical activation of feet sensory afferents could improve gait and modify the response of cardiovascular autonomic control to stressors in 16 patients (age 66 ± 2 yr) with idiopathic PD (Hoehn & Yhar scale 2-3) on their usual therapy. Eight subjects (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
(56 reference statements)
3
32
1
2
Order By: Relevance
“…A similar improvement in stride length was observed in PD compared to the control group in our study, confirming that plantar stimulation may improve postural instability seen in PD [14,36]. Recent studies have shown that punctual pressure in two specific areas of each foot (bottom-up rehabilitation) is sufficient to improve gait and stability in PD patients [19][20][21][22].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar improvement in stride length was observed in PD compared to the control group in our study, confirming that plantar stimulation may improve postural instability seen in PD [14,36]. Recent studies have shown that punctual pressure in two specific areas of each foot (bottom-up rehabilitation) is sufficient to improve gait and stability in PD patients [19][20][21][22].…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, a descriptive analysis was also performed for the qualitative variables, based on frequency distributions. The Kolmogorov-Smirnov test revealed non-normal data distribution for Previous studies investigated the responsiveness of mechanical peripheral stimulation on specific areas of the foot (first metatarsal head, plantar surface of big toe); thus, reducing motor symptoms by stimulating the somatosensory system [19][20][21][22]31]. In such studies, results were compared with age-matched control groups in order to identify differences in gait pattern between PD patients and healthy subjects.…”
Section: Swing Phase (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment consists in 4 cycles, whereas cycle means the sequential stimulation of the 4 target areas for the duration of 6 seconds each, with no intervals in between; consequently a single cycle has duration of 24 seconds, while the overall treatment including four cycles lasts 96 seconds. The trials were conducted in an isolated room to keep the treatment blind to the clinicians and neuro-radiologists involved in the study [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that mechanical stimulation of the soles of the feet improves gait performance in PD [ 30 31 ]. Quantitative measures of gait analysis parameters have shown to increase step length and gait velocity together with autonomic sympathetic modulation in PD patients 24h after automatic mechanical peripheral stimulation (AMPS) [ 32 ]. More recently, PD patients have shown improvement of their ability to perform the Timed Up and Go Test after AMPS [ 33 ] and clinical benefits are maintained up to 10 days after the last treatment [ 34 ].…”
Section: Introductionmentioning
confidence: 99%